2003
DOI: 10.1053/jlts.2003.50133
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of psychiatric disorders in liver transplantation candidates: Logistic regression models

Abstract: This study has two goals. The first goal is to assess the prevalence of psychiatric disorders in orthotopic liver transplantation (OLT) candidates by means of standardized procedures because there has been little research concerning psychiatric problems of potential OLT candidates using standardized instruments. The second goal focuses on identifying predictors of these psychiatric disorders. One hundred sixty-five elective OLT candidates were assessed by our unit. O rthotopic liver transplantation (OLT) is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 35 publications
2
37
1
Order By: Relevance
“…However, it remains unclear why up to 50% of patients with noncirrhotic CLD have these disorders long before the occurrence of cirrhosis 25 . Although this psychiatric comorbidity is common in all CLD, most of the published studies are based on an estimate of depression and anxiety in liver transplant candidate or patients after liver transplatation 7,29,14,15,27 , and patients with chronic viral hepatitis [28][29][30] . As reported in the literature, there is no difference in the level of depression and anxiety among candidates for liver transplantation and patients with liver disease who are not on the list for transplantation 24 , and therefore we estimate that the scores for depression and anxiety between these two groups of patients are comparable 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it remains unclear why up to 50% of patients with noncirrhotic CLD have these disorders long before the occurrence of cirrhosis 25 . Although this psychiatric comorbidity is common in all CLD, most of the published studies are based on an estimate of depression and anxiety in liver transplant candidate or patients after liver transplatation 7,29,14,15,27 , and patients with chronic viral hepatitis [28][29][30] . As reported in the literature, there is no difference in the level of depression and anxiety among candidates for liver transplantation and patients with liver disease who are not on the list for transplantation 24 , and therefore we estimate that the scores for depression and anxiety between these two groups of patients are comparable 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies have been focused on depression in CLD 4,6,7,12,[14][15][16][17] , while only a few have been devoted to anxiety in these patients 6,14,16,17 . Published studies data were heterogenic, both in terms of study population, different diagnostic criteria and assessment instruments that were used for the diagnosis of depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found adjustment disorder as the most common psychiatric disorder among pretransplantation patients. In a larger sample of LT candidates, Rocca et al [8] similarly pointed out that 33% of their patients waiting for LT had adjustment disorder as the most common psychiatric disorder. They also found the prevalence of psychiatric disorders in their LT candidates as 43%.…”
Section: Discussionmentioning
confidence: 99%
“…In one study approximately half of the patients who were candidates for heart or liver transplantation had at least one psychiatric disorder, and candidates for liver transplantation were found to have the highest psychiatric comorbidity prevalence [7]. Rocca et al [8] reported that 43% of their LT candidates had a current psychiatric diagnosis and Child-Pugh score and previous psychiatric diagnosis were found as significant independent predictors of depressive disorders. Among psychiatric disorders in their LT candidates, adjustment disorder was found particularly prevalent.…”
mentioning
confidence: 99%
“…A number of studies have shown that the severity of the liver diseases is an important predictor of the severity of psychiatric disorders. The Child-Pugh classification 8 is one reliable predictor for the occurrence of depression and other symptoms such as, sleep and sexual disorders, fatigue and history of psychiatric diseases 1,9 . This instrument provides a prognostic classification made from two clinical data: ascites and hepatic encephalopathy, and three laboratory findings: levels of total bilirubin, albumin and activity of prothrombin.…”
mentioning
confidence: 99%